High-resolution X-ray diffraction analysis of strain distribution in GaN nanowires on Si(111) substrate - Stanchu, Hryhorii; Kladko, Vasyl; Kuchuk, Andrian V; Safriuk, Nadiia; Belyaev, Alexander; Wierzbicka, Aleksandra; Sobanska, Marta; Klosek, Kamil; Zytkiewicz, Zbigniew R (Nanoscale research letters, 2015)
In this work, the influence of micro- and macro-deformation profiles in GaN nanowires (NWs) on the angular intensity distribution of X-ray diffraction are studied theoretically. The calculations are performed by using kinematical theory of X-ray diffraction and assuming the deformation decays exponentially from the NW/substrate interface. Theoretical modeling of X-ray scattering from NWs with different deformation profiles are carried out. We show that the shape of the (002) 2θ/ω X-ray diffraction profile (XDP) is defined by initial deformation at the NW's bottom and its relaxation depth given by the decay depth of the exponential deformation profile. Also, we demonstrate that macro-deformation leads to XDP shift, whereas micro-deformations are the cause of XDP's asymmetry and its symmetrical broadening. A good correlation between calculated and experimental XDP from self-assembled GaN NWs on Si(111) substrate was achieved by taking into account all parameters of micro- and macro-deformation profiles.